Defeating Antibiotic- and Phage-Resistant Enterococcus faecalis Using a Phage Cocktail in Vitro and in a Clot Model - Khalifa, Leron; Gelman, Daniel; Shlezinger, Mor; Dessal, Axel Lionel; Coppenhagen-Glazer, Shunit; Beyth, Nurit; Hazan, Ronen (Frontiers in Microbiology, 2018)
The deteriorating effectiveness of antibiotics is propelling researchers worldwide towards alternative techniques such as phage therapy: curing infectious diseases using viruses of bacteria called bacteriophages. In a previous paper, we isolated phage EFDG1, highly effective against both planktonic and biofilm cultures of one of the most challenging pathogenic species, the vancomycin-resistant Enterococcus (VRE). Thus, it is a promising phage to be used in phage therapy. Further experimentation revealed the emergence of a mutant resistant to EFDG1 phage: EFDG1r. A disastrous occurrence in the development of antibiotic resistance, it proved only a minor hindrance in phage development. We quickly and successfully isolated a new phage, EFLK1, which proved effective against both the resistant mutant EFDG1r and its parental VRE, E. faecalis V583. Furthermore, combining both phages in a cocktail produced an additive effect against E. faecalis V583 strains regardless of their antibiotic or phage-resistance profile. An analysis of the differences in genome sequence, genes, mutations and tRNA content of both phages is presented. This work is a proof-of-concept of one of the most significant advantages of phage therapy, namely the ability to easily overcome emerging resistant bacteria.